The Effect of Domestic Investment and Foreign Investment and Labor on The Gross Regional Domestic Product of Regencies in East Kalimantan - Kantrianus Balur; Fitriadi (FEB Universitas Mulawarman, 2026)
The purpose of this study is to determine the influence of domestic investment, foreign investment and labor on gross regional domestic product. The data used is secondary data in the form of data on the realization of domestic investment, the realization of foreign investment, and the number of labor forces working in 10 districts/cities of East Kalimantan in the period 2017-2023. The analysis model used was a regression of panel data processed using Eviews-12. The results of the study show that domestic investment, foreign investment, and labor have a positive and significant influence on the gross regional domestic product of districts/cities in East Kalimantan